Ways to Increase the Effectiveness of Mechanisms for Regulating the Rural Labor Market - Ulug'murodova, N. B.; Rashidov, A. U. (Research Parks Publishing LLC, 2022)
The article develops the concept of regulating the rural labor market, employment, increasing the competitiveness of the workforce, organizational improvement of employment services, achieving a balance between supply and demand for labor, a flexible labor market, employment of the rural population through human capital development.